Studies on antibacterial activity of some plant extracts - Taley, S L; Pethe, A S; Rothe, S P (International Multidisciplinary Research Journal, 2013)
The antibacterial activity of the extracts of Melia azedarch (L), Spilanthes paniculata (L, f), Oxalis Corniculata, Colocassic esculenta (L), and Hyptis suaveolens (L) were evaluated against five bacteria isolated from semen samples (E. coli., S. aureus, P. vulgaris, P. aeruginosa and B. subtilis). These plants are used in medicine to treat infections of microbial origin.